The Influence of Accounting Information Systems on Internal Control of Receivables: Study at one of the telecommunications companies in Bandung - Adriana Florenciana Amnain; Vicky Achmad Zulfikar; Jimmy Rusjiana (Electronic, Business, Management and Technology Journal, 2023)
This study aims to investigate the impact of variables related to the accounts receivable accounting information system and accounts receivable internal control on a telecommunications company located in Bandung. Based on the obtained calculation results, it has been determined that the accounting information system for accounts receivable can be classified as moderately satisfactory. At the same time, the internal control measures for accounts receivable can also be classified as moderately satisfactory. The research findings indicate a significant correlation of 0.840 between variables X and Y, suggesting a strong relationship between the accounts receivable accounting information system and accounts receivable internal control. According to the analysis conducted using simple linear regression, it has been shown that the relationship between the dependent variable Y and the independent variable X, representing accounts receivable in the accounting information system, can be expressed as Y = 7.180 + 0.729X. This condition implies that for each unit rise in the accounts receivable; there is an associated increase of 0.729 units in the dependent variable. The coefficient analysis reveals that the accounts receivable accounting information system significantly contributes to the internal control of accounts receivable, accounting for 70.6% of the overall influence. The remaining 29.4% can be attributed to various other factors.